Statistične metode z računalnikom za pedagoge - Bratina, Tomaž (University of Maribor Press, 2021)
Statistical Methods by Computer for Pedagogues. The publication intention is to present the properties, purpose, and use of statistical methods in pedagogical research. The presentation of each statistical method includes a short theoretical explanation and a video explaining the procedures required to perform statistical data processing with the selected statistical method in the SPSS program, including the detailed interpretation of the outcomes. The outcome is available to the user as an SPSS source file and as a universal text file. The publication enables the storage of files showing outcomes and data files used in the interpretations. Both allow the subsequent independent execution of the same statistical processing and comparisons.